Risk factors for noncontact anterior cruciate ligament injury in female high school basketball and handball players: A prospective 3-year cohort study - Nakase, J.; Kitaoka, K.; Shima, Y.; Oshima, T.; Sakurai, G.; Tsuchiya, H. (Asia Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2020)
Introduction: The risk factors of noncontact anterior cruciate ligament (ACL) injury remain an enigma. The purpose of this study was to prospectively evaluate the risk factors for noncontact ACL injury in female high school basketball and handball players. Materials and Methods: We conducted a 3-year prospective cohort study between 2009 and 2014, and it included 317 female high school athletes aged 15 years. At baseline, they underwent detailed examinations for various parameters that were documented during their first year of high school. The parameters assessed were height (cm), weight (kg), general joint laxity (points), navicular drop (mm), anterior laxity of the knee using the KT-1000 Knee Ligament Arthrometer (mm), angle of femoral anteversion (º), knee extensor/flexor muscle strength (Nm/kg), and hip abductor strength (Nm/kg). All ACL injuries that occurred during these 3 years were recorded. Results: Of 317 players, 27 were excluded because they either had a history of ACL injury or could not complete the study. Thirty ACL tears occurred. Three of the ACL injuries were contact injuries, whereas the remaining 27 were noncontact injuries. Greater body weight (95% confidence interval [CI], 1.030-1.174; P = 0.004), a high hip abductor strength (95% CI, 1.462-4.827; P = 0.001), and small femoral anteversion (95% CI, 0.746-0.982; P = 0.027) were found to be risk factors in logistic regression analysis. Conclusion: Greater body weight, a high hip abductor strength, and small femoral anteversion were risk factors for noncontact ACL injury in female high school basketball and handball players.